Passing the written DMV test [videorecording (DVD)] - Powell, Charles (Powell Productions, 2005)
This videodisc provides the information needed to pass the written DMV test. It gives the fundamentals of safe driving without giving the specific rules of each state. Viewers can choose by state to see obvious differences in the driving rules of the states.